Direct contact evaporation heat transfer coefficient and drobble size distribution in a 2D column. (5th March 2016) - Fu, Hailing; Wang, Yiping; Huang, Qunwu; Cui, Yong; Sun, Yong; Jiang, Lihong
Highlights: The statistical characteristics of n-pentane drobble size distribution were studied. The Sauter mean diameter was analysed by considering break-up and coalescence. The area of drobble liquid–liquid heat transfer interface was measured. The influence factors of heat transfer coefficient were analysed. Abstract: This work presents an experimental study of the n-pentane evaporation process in hot water to investigate the behaviour of drobbles and the performance of direct contact heat transfer. The evaporating drobble size distribution (DSD), Sauter mean diameters, interfacial areas of liquid–liquid heat transfer and n-pentane evaporation rate are measured at different n-pentane inlet flowrates and water temperatures. At the bottom of the 2D column, the probability density function (PDF) has a unimodal shape at a water temperature of 45 °C and has a bimodal shape at a relatively high water temperature of 55 °C. The Sauter mean diameter of the drobbles increases with increasing water temperature and height of the test position. The liquid–liquid heat transfer interfacial area decreases upon increasing the testing height and water temperature. The heat transfer coefficient of a single drobble has a large dependence upon the rising velocity.